Germany's policy towards the state of Syria from the eighties of the nineteenth century until the beginning of the twentieth century (Journal of the College of Basic Education, 2022)
This study is based on the search in the following axes:First: The beginnings of Germany activity in SyriaSecond: The forms of Germany of the different fields in SyriaThird : The visit of Germanic Emperor to Damascus & its resultsThe study is focusing on a historical demonstration for the beginnings of Germany activity in Syria and identifying the nature of its interests which pat the foundation bricks or the roots of this activity and upon which the economical, military, and political relations, as well it showed clear image of the many forms of the Germanic penetration in to Syria especially after the German Emperor William II took the lead and who took many economical and political advantages and that led to increase the competition for the estates of the ottoman state especially Britain which was in fear over its commercial interests in India and the east.Likewise the German trend toward the middle east region and especially Syria came somehow late, since the eighties of the Nineteenth century, due to Germany occupation in arranging its internal affairs, and its latten in the ear of the industrial revolution, for this its entering to colonize movement came late, despite that it was able to create big interest for itself in the Ottoman state and to became a colonist power and have global colonists.